Inhaled Corticosteroid phobia among parents of Egyptian asthmatic children - Amira SA. Said; Nadia Hussain; Lamiaa N. Abdelaty; Amal HI. Al Haddad; Abdullah Abu Mellal (Elsevier, 2021)
Background: Inhaled Corticosteroid therapy is the cornerstone of asthma treatment. Yet, the reported prevalence of steroid phobia among parents of asthmatic children has been concerning. This study aimed to assess the impact of steroid phobia on ICS adherence, and asthma management. Method: A multicenter, cross-sectional study was held among 500 parents of asthmatic children over 12-months. Each participant completed a structured questionnaire that recorded patients' demographic data, and explored participants' main concerns regarding ICS. Additionally, participants level of asthma control was assessed by the Arabic childhood asthma control test C-ACT. Result: Of 500 interviewed asthmatic children, up to 66.6% reported having ICS fears, yet only 25.8% reported discussing their concerns with their healthcare providers. In addition, over 50% of parents reported requesting ICS sparing. Regarding ICS adherence, a significant difference (<0.001) was reported as 33.3% vs 40.1% for concerned and non-concerned parents respectively. Participants with ICS fears had children with significantly (<0.001) lower mean C-ACT scores of 33.3% versus 46.7% for those with no fear, respectively. In addition, Request for ICS sparing was reported as 61.5% vs 53.9% for concerned and non-concerned parents respectively. However, asthma severity and discussing ICS concerns was not significantly affected by ICS fear. Conclusion: This study suggests that steroid phobia is a significant factor that influence ICS adherence and asthma control. Proper asthma education should be targeted to alleviate unjustifiable steroid use concerns. Future research should be more oriented to crafting proper interventional strategies to better address the ICS negative perceptual barriers